Metal sulfide ion exchanger / collagenous fiber composite aerogel, preparation method thereof and application of metal sulfide ion exchanger / collagenous fiber composite aerogel in removal of Sr < 2 + > ions in aqueous solution
By interweaving the metal sulfide ion exchanger with collagen fibers into a composite aerogel, the problem of difficult operation and difficulty in recycling of metal sulfide ion exchangers in the prior art is solved, and efficient adsorption and convenient recovery of Sr2+ ions are achieved.
Patent Information
- Application Number
- CN202411548039.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing metal sulfide ion exchangers are difficult to operate, difficult to recover in practical applications, and are difficult to effectively remove Sr2+ ions in aqueous solutions.
A metal sulfide ion exchanger/collagen fiber composite aerogel is developed to form a composite material that is easy to operate and convenient to recover by interweaving the metal sulfide ion exchanger with collagen fibers into a sponge-like bulk material.
It realizes efficient adsorption of Sr2+ ions, with fast adsorption kinetics, wide pH adsorption activity range, good selectivity, strong operability and easy recovery, and is suitable for treating radioactive wastewater containing strontium ion.
Smart Images

Figure CN119701877A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a metal sulfide ion exchanger / collagen fiber composite aerogel and a preparation method thereof and a method for removing Sr from aqueous solution. 2+ The application of ions belongs to the field of new material technology. Background Art
[0002] In a nuclear reactor, 90 Sr is 235 The fission product of U has a long half-life (t 1 / 2 = 28.8 years), high fission yield (5.89%), and strong radioactivity (high β-decay energy) and are considered to be a highly dangerous radionuclide (Sci. Total Environ. 2021, 76(4), 144-266). 90 Sr is usually present in ionic form (Sr 2+ ) exists in radioactive waste liquids and has high solubility and mobility. Therefore, it can be easily transferred to the environment. For example, in a nuclear accident, a large amount of 90 Sr was released, causing the total radioactivity level in fish in nearby waters to exceed the limit (100 Bq / kg). 2+ The chemical properties of Ca 2+ Similar, therefore, it will accumulate in human bone tissue, leading to diseases such as leukemia or cancer (Chem. 2019, 5(4), 977-994). 90 Sr can also be used as a radioactive source in cancer treatment and coal resource exploration. Therefore, it is very important to capture Sr from complex radioactive waste water. 90 Sr is of great significance.
[0003] There are many methods for removing Sr 2+ Ions, such as chemical precipitation, solvent extraction, membrane filtration and ion exchange / adsorption (Acta 1998, 81 (4), 201-206). Among them, ion exchange is considered to be one of the most ideal methods because of its simple operation and high removal efficiency. Metal sulfide ion exchangers are a new type of ion exchange material developed in recent years. They show high adsorption capacity, fast kinetics and high selectivity for the capture of radionuclides. This is due to the flexible framework of metal sulfide ion exchangers and the soft Lewis base S 2- The strong interaction between the site and the radioactive metal ions. However, most metal sulfide ion exchangers currently exist mainly in the form of powdered crystals, which are difficult to recover from the solution, difficult to operate, and difficult to apply in practice. Therefore, it is urgent to develop a new composite material that is easy to operate and can be easily recycled for efficient and rapid removal of Sr from aqueous solutions. 2+ ion. Summary of the invention
[0004] In order to solve the problem that existing metal sulfide ion exchangers are difficult to operate and recycle in practical applications, the present application provides a technical solution for preparing metal sulfide ion exchanger / collagen fiber composite aerogels, and develops a simple, economical and environmentally friendly new preparation method for metal sulfide ion exchanger-based composite materials. The prepared composite materials with regular shapes and easy operation can be applied to radioactive Sr 2+ Removal of ions.
[0005] This application adopts the following technical solutions:
[0006] According to one aspect of the present application, a metal sulfide ion exchanger / collagen fiber composite aerogel is provided, wherein the metal sulfide ion exchanger / collagen fiber composite aerogel is a sponge-like block material;
[0007] The spongy bulk material is composed of metal sulfide ion exchangers and collagen fibers interwoven together;
[0008] The chemical formula of the metal sulfide ion exchanger is A x M y M' y' S z ;
[0009] Wherein, A is an alkali metal or a protonated organic amine cation, M is a Group IIIA element, M' is an Group IVA element, S is sulfur, x ranges from 1 to 4, y ranges from 1 to 4, y' ranges from 1 to 4, and z ranges from 2 to 8.
[0010] Optionally, the size of the sponge-like block material is 1 cm to 8 cm.
[0011] Optionally, the chemical formula of the metal sulfide ion exchanger is KInSnS4.
[0012] According to another aspect of the present application, a method for preparing the above-mentioned metal sulfide ion exchanger / collagen fiber composite aerogel is provided, comprising the following steps:
[0013] S1. Obtaining metal sulfide ion exchanger A x M y M' y' S z ;
[0014] S2, respectively obtain metal sulfide ion exchanger A x M y M' y' S z Suspension, collagen fiber suspension;
[0015] S3, the metal sulfide ion exchanger A in step S2 x M y M' y' S z The suspension and the collagen fiber suspension are mixed and stirred to obtain a composite flocculent;
[0016] S4, washing the composite floccules from step S3 with water until the supernatant is clear, and then freeze-drying the composite floccules to obtain the metal sulfide ion exchanger / collagen fiber composite aerogel.
[0017] In this application, metal sulfide ion exchanger A is obtained. x M y M' y' S z The method can be achieved by various methods, such as a hydrothermal method or a vacuum solid phase method.
[0018] Alternatively, obtain a metal sulfide ion exchanger A x M y M' y' S z The method comprises step S1-a:
[0019] The raw material containing cations of alkali metal or protonated organic amine, S source, IIIA group metal source, IVA group metal source are reacted to obtain metal sulfide ion exchanger A. x M y M' y' S z .
[0020] Optionally, the metal source of group IIIA elements is selected from In powder, the metal source of group IVA elements is selected from Sn powder, the raw material of alkali metal or protonated organic amine cation is selected from potassium carbonate, and the S source is selected from sulfur powder.
[0021] Optionally, the raw material of the cation of the alkali metal or protonated organic amine, the S source, the metal source of the IIIA group element and the metal source of the IVA group element are in the form of a chemical formula A x M y M' y' S z The molar ratio of the elements in the reaction is not strictly limited, and those skilled in the art can adjust it according to needs.
[0022] Alternatively, obtain a metal sulfide ion exchanger A x M y M' y' S z The method comprises step S1-b:
[0023] Will contain A a Mb S c The mixture of the material, the S source and the IVA group element metal source is ground and then reacted in a vacuum atmosphere to obtain a metal sulfide ion exchanger A. x M y M' y' S z ;
[0024] Among them, the value range of a is 1 to 3, the value range of b is 1 to 3, and the value range of c is 2 to 4.
[0025] Optionally, in step S1-b, the reaction conditions include: reacting at a reaction temperature of 700°C to 800°C for 80h to 120h, then reducing the temperature to 500°C to 600°C within 60h to 80h, and naturally cooling to room temperature after the reaction is completed.
[0026] Optionally, in step S1-b, the metal source of the IVA group element is selected from Sn powder, and the S source is selected from sulfur powder.
[0027] Optionally, in step S1-b, A a M b S c The material, S source and IVA group metal source are represented by the chemical formula A x M y M' y' S z The molar ratio of the elements in the reaction is not strictly limited, and those skilled in the art can adjust it according to needs.
[0028] In this application, A a M b S c The material preparation method can be achieved by a variety of methods, and those skilled in the art can choose according to their needs.
[0029] Optionally, obtain A a M b S c Materials methods include S1-a:
[0030] The raw materials containing S source, IIIA group metal source and alkali metal or protonated organic amine cation are placed in a sealed container for reaction to obtain A a M b S c Material.
[0031] Optionally, in step S1-a, the metal source of the group IIIA element is selected from In powder, the raw material of the cation of the alkali metal or protonated organic amine is selected from potassium carbonate, and the S source is selected from sulfur powder.
[0032] Optionally, in step S1-a, the reaction conditions include: reaction temperature of 210°C to 230°C, and reaction time of 36h to 72h.
[0033] Optionally, in step S1-a, the raw materials of the S source, the metal source of the group IIIA element and the cation of the alkali metal or protonated organic amine are of the chemical formula A a M b S c The molar ratio of the elements in the reaction is not strictly limited, and those skilled in the art can adjust it according to needs.
[0034] Optionally, in step S2, the metal sulfide ion exchanger A x M y M' y' S z The suspension is obtained by the following method: metal sulfide ion exchanger A x M y M' y' S z Mix with water, dilute to volume after ball milling.
[0035] Optionally, in step S2, A x M y M' y' S z The concentration of the suspension is 4g / L to 6g / L.
[0036] Optionally, in step S2, the collagen fiber suspension is obtained by the following method: mixing collagen fibers and water, and then diluting and fixing the volume after ball milling.
[0037] Optionally, in step S2, the concentration of the collagen fiber suspension is 8 g / L to 12 g / L;
[0038] In this application, ion exchanger A x M y M' y' S z The suspension is made of collagen fibers to facilitate the formation of composite floccules.
[0039] Optionally, in step S2, the ball milling time is 12 h to 16 h, and the ball milling speed is 400 r / min to 500 r / min.
[0040] Optionally, in step S3, the stirring conditions include: the stirring time is 2h to 5h.
[0041] Optionally, in step S3, the metal sulfide ion exchanger A in the composite flocculent x M y M' y' S z, the weight ratio of collagen fibers is 0.5~1.25:1.
[0042] Optionally, in step S4, the freeze-drying conditions include: the drying time is 50 hours to 70 hours.
[0043] According to another aspect of the present application, there is also provided a metal sulfide ion exchanger / collagen fiber composite aerogel obtained according to the above preparation method as an adsorption material for removing Sr from an aqueous solution. 2+ Application of ions.
[0044] Optionally, the application includes:
[0045] The metal sulfide ion exchanger / collagen fiber composite aerogel is mixed with Sr 2+ The ions come into contact with the solution and adsorb;
[0046] The contact is dynamic contact and / or static contact.
[0047] Optionally, containing Sr 2+ Sr in ion solution 2+ The concentration of ions is 5.29 mg / L~235.33 mg / L.
[0048] Optionally, containing Sr 2+ The pH of the ionic solution is 2-12.
[0049] Optionally, the contact conditions include: the contact temperature is 20°C to 35°C.
[0050] Optionally, when the contact is static contact, the contact conditions include: the contact time is 6 hours to 12 hours.
[0051] Optionally, when the contact is dynamic contact, the Sr-containing 2+ A solution of ions is passed through an adsorption column;
[0052] The adsorption column is filled with the metal sulfide ion exchanger / collagen fiber composite aerogel.
[0053] The beneficial effects of this application include:
[0054] The preparation method of the metal sulfide ion exchanger / collagen fiber composite aerogel provided in the present application has a very simple operation process and can be prepared in large quantities. The process does not involve the use of toxic materials and has low requirements for experimental equipment. The metal sulfide ion exchanger / collagen fiber composite aerogel prepared in the present application can convert the metal sulfide ion exchanger A x M y M' y' S zThe effective combination with collagen fibers greatly promotes the convenience of material operation and solves the existing metal sulfide ion exchanger A x M y M' y' S z The problem of practical operation and recovery from aqueous solution was solved, and the recycling of leather industry waste (the source of collagen fibers) was realized. In addition, the composite aerogel has a good effect on Sr 2+ The removal of ions has the characteristics of fast adsorption kinetics, wide pH adsorption activity range, good selectivity, strong operability and easy recovery, which has broad application prospects for the disposal of radioactive wastewater containing strontium ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 These are actual photos of sample 3 from different angles.
[0056] Figure 2 Scanning electron microscope images (SEM) of samples 1 to 3, where (a) is sample 1, (b) is sample 2, and (c) and (d) are sample 3.
[0057] Figure 3 The X-ray powder diffraction patterns (PXRD) of samples 1, 2 and 3 are shown in FIG.
[0058] Figure 4 Removal of Sr for sample 3 2+ Kinetic diagram of ions.
[0059] Figure 5 Removal of Sr for sample 3 2+ Isothermal adsorption of ions.
[0060] Figure 6 The Sr content of sample 3 in a wide pH range 2+ Plot of the partition coefficient and removal efficiency of ions.
[0061] Figure 7 For sample 3, Sr is adsorbed in the column 2+ ion data diagram, where (a) is the Thomas model fitted sample 3 to remove Sr 2+ Ion penetration curve; (b) is the removal of Sr from sample 3 during column adsorption. 2+ Ion removal rate diagram.
[0062] Figure 8 Sr was artificially added to sample 3. 2+ Removal of Sr from real water samples 2+ Plot of the partition coefficient and removal efficiency of ions. DETAILED DESCRIPTION
[0063] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0064] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0065] The collagen fiber comes from the scraps generated in the leather industry production and is purchased from Shenzhen Yongshengye Textile Trading Co., Ltd., product number Y051.
[0066] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0067] The model of the scanning electron microscope (SEM) was JEOL JSM-6700F.
[0068] The models of inductively coupled plasma mass spectrometry (ICP-MS) and inductively coupled plasma optical emission spectrometry (ICP-OES) were XSerise II and Thermo 7400.
[0069] X-ray powder diffraction (XRD) phase analysis was carried out on a Miniflex II X-ray diffractometer.
[0070] The distribution coefficient in the examples of the present application is calculated by the following method:
[0071]
[0072] The removal rate in the examples of this application is calculated by the following method:
[0073]
[0074] In the above formula, C0 and C e represent the initial concentration and equilibrium concentration of cesium solution, K d and represents the distribution coefficient of the ion.
[0075] For the sake of simplicity, in the examples of the present application, the metal sulfide ion exchanger KInSnS4 is named as sample 1, the collagen fiber is named as sample 2, and the metal sulfide ion exchanger KInSnS4 / collagen fiber composite aerogel is named as sample 3.
[0076] Example 1 Preparation of Metal Sulfide Ion Exchanger / Collagen Fiber Composite Aerogel
[0077] Step S1. First, K2CO3 (9 mmol), S powder (9 mmol), In powder (30 mmol) and deionized water (1.5 mL) were mixed and stirred evenly according to the stoichiometric ratio, and then placed in a polytetrafluoroethylene reactor and kept in an oven at 220°C for 2 days to obtain KInS2 material. Then, KInS2 (3 mmol), S powder (6 mmol) and Sn powder (3 mmol) were mixed evenly in a mortar according to the stoichiometric ratio, and then transferred to a quartz tube for vacuum sealing, and placed at a furnace temperature of 750°C for 4 days, and the furnace was turned off after the temperature was reduced to 550°C within 3 days. Sample 1 was obtained after the furnace temperature was reduced to room temperature.
[0078] Step S2, using ball milling to reduce the particle size of sample 1 and sample 2 so that they can be better suspended in water: 5 mL of deionized water, 0.5 g of sample 1 and zirconium beads are put into a ball mill, and ball milled at a speed of 400 r / min for 16 hours. After the end, the ball-milled suspension in the ball mill is transferred and diluted with deionized water to obtain a ball-milled suspension of 5 g / L sample 1; 6 mL of deionized water, 0.40 g of sample 2 and zirconium beads are put into a ball mill, and ball milled at a speed of 400 r / min for 16 hours. After the end, the ball-milled suspension in the ball mill is transferred and diluted with deionized water to obtain a ball-milled suspension of 10 g / L sample 2.
[0079] Step S3, 100 mL of the ball-milled suspension of sample 1 (5 g / L) and 40 mL of the ball-milled suspension of sample 2 (10 g / L) were mixed and stirred for 2 hours to obtain a uniform sample 1 / sample 2 composite flocculent.
[0080] Step S4, repeatedly washing the floccules with deionized water until the supernatant becomes clear. Then, the floccules are rapidly frozen with liquid nitrogen and freeze-dried for 60 hours to obtain a large-sized, regular-shaped, bright yellow sponge-like metal sulfide ion exchanger / collagen fiber composite aerogel, i.e., sample 3 (as shown in the actual picture). Figure 1 shown).
[0081] Test Example 1 Characterization of Samples 1 to 3
[0082] Scanning electron microscopy revealed that sample 1 was flaky ( Figure 2 a), sample 2 is in the form of fiber bundles ( Figure 2 b), sample 3 is an interwoven "network" morphology ( Figure 2 c-2d). In addition, the PXRD patterns of sample 1, sample 2 and sample 3 are as follows: Figure 3 As shown. Since collagen fibers are amorphous structures, no obvious diffraction peaks are observed in their PXRD patterns, while characteristic Bragg peaks corresponding to sample 1 appear in the PXRD pattern of sample 3, indicating that sample 1 and sample 2 are successfully combined.
[0083] Test Example 2 Adsorption kinetics test of sample 3
[0084] Sample 3 was mixed with a certain initial concentration of Sr 2+ The ion solutions were mixed and stirred at room temperature according to the condition of m (mass of exchange agent): V (volume of solution) = 1 g / L. A small amount of supernatant was taken at regular intervals and the ion concentration was measured by inductively coupled plasma emission spectroscopy. The test results are as follows: Figure 4 As shown in Table 1, sample 3 has a 2-minute Sr 2+ The adsorption of ions has basically reached equilibrium.
[0085] Table 1. Sr removal in solution by sample 3 2+ Kinetic results of ions
[0086]
[0087]
[0088] Test Example 3 Sample 3 for Sr 2+ Ion adsorption isotherm test model
[0089] Sample 3 was mixed with different initial Sr 2+ The solution of ions was mixed. According to the condition of m (mass of exchange agent): V (volume of solution) = 1 g / L, the mixture was shaken at room temperature for 12 hours. After the adsorption was completed, the supernatant and the initial solution were taken and Sr was determined by inductively coupled plasma emission spectroscopy. 2+ The experimental results are as follows: Figure 5 As shown in Table 2, the Langmuir-Freundlich model fits the Sr 2+ The maximum adsorption capacity of ions is 41.80 mg / g.
[0090] Table 2. Sr removal in solution by sample 3 2+ Isothermal adsorption results of ions
[0091] Initial concentration (mg / L) Equilibrium concentration (mg / L) Adsorption capacity (mg / g) 7.23 0.0011 7.23 14.58 0.075 14.50 30.00 0.94 29.06 63.78 26.76 37.02 95.69 59.14 36.55 235.33 196.73 38.60
[0092] Test Example 4: Removal of Sr from Sample 3 at different pH values 2+ Ion Capacity Test
[0093] Sample 3 was mixed with Sr at different pH values. 2+ The ion solution was mixed and the reaction was carried out in a shaker at room temperature for 12 h under the condition of m (exchanger mass): V (solution volume) = 1 g / L. After the adsorption was completed, the supernatant and the initial solution were taken and Sr was determined by inductively coupled plasma emission spectroscopy. 2+ The results are as follows: Figure 6 As shown in Table 3, the removal solution provided by the present application contains Sr2+ The ion method can effectively remove Sr in a wide pH range. 2+ ion.
[0094] Table 3. Removal of Sr from Sample 3 in different pH solutions 2+ The results of ions
[0095]
[0096]
[0097] Test Example 5 Application of Sample 3 Simulated Adsorption Column
[0098] A 50 μm sieve plate was placed at the bottom of a polyethylene column with a diameter of 0.56 cm, and then 0.1 g of sample 3 was injected into the column to a height of about 3 cm. Sr was pumped into the column at a flow rate of 0.4 mL / min using a peristaltic pump. 2+ The solution (10.43 mg / L) was pumped into the column, and the effluent was collected every 5 minutes using an automatic collector. The concentration at the intermediate moment was regarded as the concentration in the tube.
[0099] Figure 7 a is the simulated adsorption column of sample 3 for Sr 2+ The breakthrough curve of the ion solution conforms to the Thomas model, and the maximum uranium adsorption is 58.64 mg / g. Figure 7 b is the Sr content of sample 3 in the column experiment 2+ The removal rate of ions was still above 99.28% when the breakthrough point was 123 bed volumes. This shows that sample 3 can be used as column filler to remove Sr 2+ Dynamic adsorption of ions. See Table 4 for specific data:
[0100] Table 4. The removal of Sr-containing adsorption column using sample 3 as column filler 2+ Solution results of ions
[0101]
[0102]
[0103] Test Example 6 Sample 3 was added with simulated radioactive Sr 2+ Removal of Sr from real water samples 2+ The results of ions
[0104] In order to determine the adsorption performance of sample 3 in actual water samples, simulated radioactive Sr 2+ The tap water, Wulong River water and Qishan Lake water were tested for Sr 2+ Ion adsorption experiment. In tap water, Wulong River water and Qishan Lake water, sample 3 has a strong affinity for Sr 2+The removal rates of ions were 92.40%, 93.94% and 77.78% respectively. Figure 8 and Table 5), indicating that sample 3 has the ability to efficiently remove Sr from complex water environments. 2+ The ability of ions.
[0105] Table 5. Sample 3 with added simulated radioactive Sr 2+ Removal of Sr from real water samples 2+ The results of ions
[0106]
[0107] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A metal sulfide ion exchanger / collagen fiber composite aerogel, characterized in that: The metal sulfide ion exchanger / collagen fiber composite aerogel is a sponge-like block material; The spongy bulk material is composed of metal sulfide ion exchangers and collagen fibers interwoven together; The chemical formula of the metal sulfide ion exchanger is A x M y M' y' S z ; Wherein, A is an alkali metal or a protonated organic amine cation, M is a group IIIA element, M' is a group IVA element, S is sulfur, x ranges from 1 to 4, y ranges from 1 to 4, y' ranges from 1 to 4, and z ranges from 2 to 8.
2. The metal sulfide ion exchanger / collagen fiber composite aerogel according to claim 1, characterized in that: The size of the sponge-like block material is 1 cm to 8 cm.
3. The method for preparing the metal sulfide ion exchanger / collagen fiber composite aerogel according to claim 1 or 2, characterized in that: The steps include: S1. Obtaining metal sulfide ion exchanger A x M y M' y' S z ; S2, respectively obtain metal sulfide ion exchanger A x M y M' y' S z Suspension, collagen fiber suspension; S3, the metal sulfide ion exchanger A in step S2 x M y M' y' S z The suspension and the collagen fiber suspension are mixed and stirred to obtain a composite flocculent; S4, washing the composite floccules from step S3 with water until the supernatant is clear, and then freeze-drying the composite floccules to obtain the metal sulfide ion exchanger / collagen fiber composite aerogel.
4. The preparation method according to claim 3, characterized in that: In step S2, the metal sulfide ion exchanger A x M y M' y' S z The suspension is obtained by the following method: metal sulfide ion exchanger A x M y M' y' S z Mix with water, dilute and fix volume after ball milling; Preferably, in step S2, the collagen fiber suspension is obtained by the following method: mixing collagen fibers and water, and diluting and fixing the volume after ball milling; Preferably, in step S2, the ball milling time is 12 h to 16 h, and the ball milling speed is 400 r / min to 500 r / min.
5. The preparation method according to claim 3, characterized in that: In step S3, the stirring conditions include: stirring time is 2h to 5h; Preferably, in step S3, the metal sulfide ion exchanger A in the composite flocculent x M y M' y' S z , the weight ratio of collagen fibers is 0.5~1.25:
1.
6. The metal sulfide ion exchanger / collagen fiber composite aerogel according to claim 1 or 2 or the metal sulfide ion exchanger / collagen fiber composite aerogel obtained by the preparation method according to any one of claims 3 to 5 is used as an adsorbent material to remove Sr from aqueous solution 2+ Application in ions.
7. The use according to claim 6, characterized in that: The applications include: The metal sulfide ion exchanger / collagen fiber composite aerogel is mixed with a Sr-containing 2+ The ions come into contact with the solution and adsorb; The contact is dynamic contact and / or static contact.
8. The use according to claim 7, characterized in that: Contains Sr 2+ Sr in ion solution 2+ The concentration of ions is 5.29mg / L~235.33mg / L; Preferably, containing Sr 2+ The pH of the solution of ions is 2 to 12; Preferably, the contact conditions include: the contact temperature is 20°C to 35°C.
9. The use according to claim 7, characterized in that: When the contact is static contact, the contact conditions include: the contact time is 6h to 12h.
10. The use according to claim 7, characterized in that: When the contact is a dynamic contact, the Sr 2+ A solution of ions is passed through an adsorption column; The adsorption column is filled with the metal sulfide ion exchanger / collagen fiber composite aerogel.
Citation Information
Patent Citations
Sol-gel process
CN101238075A
Graphene compressible aerogel on basis of chemical reduction, method for preparing graphene compressible aerogel and application thereof
CN105692607A
Preparation method of composite material
CN107331832A
Preparation method and application of composite aerogel of post-modified aminated ZIF-8 and cellulose
CN117160431A
Column material for the capture of heavy metal and precious metal ions
US20150144568A1